Analysis of the Teacher's Role in Educating Students during the Era of Disruption - Jocelyn Akhsan (Enigma in Education, 2023)
In an age characterized by the widespread integration of technology, particularly artificial intelligence (AI), into various domains, including education, the significance of instructors has grown significantly. Teachers serve not simply as conveyors of knowledge but also as mentors, catalysts, and enablers in navigating the intricacies and unpredictability that impact the realm of education. A literature search was done using several databases, such as PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar, to find out how teachers can have a big impact on the future of education and help students learn how to adapt to a changing world. Amidst a period of significant change, teachers play a vital role as educators, mentors, motivators, and facilitators. Their contribution is essential in ensuring that education stays pertinent and impactful and equips students with the necessary skills to navigate swift transformations. Teachers bear the principal duty of imparting pertinent knowledge, skills, and values that encompass a comprehension of AI technology. Additionally, they serve as mentors, assisting students in developing academic and professional objectives, and as motivators, fostering students' passion for acquiring knowledge. Furthermore, teachers serve as facilitators, empowering students to incorporate AI technology and other digital resources into their learning journey.